Implementasi Nilai-nilai Al-Qur’an Dalam Induk Undang Nan Limo - Marwiyah, Siti; Ghaffar, Abdul; Musli, Musli (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article examines the implementation of Al-Qur'an values in a set of Jambi local wisdom as per the familiar saying,